THE IMPACT OF MODERN ANTIEPILEPTIC DRUGS ON THE QUALITY OF LIFE OF PATIENTS WITH EPILEPSY - Abdurahmanov.I. I.; Bo‘stonov.O. Y. (Scholars Digest Publishing, 2024)
The study included general clinical and neurological examination, EEG and/or video EEG monitoring, RCT and/or MRI of the brain, neuropsychological testing using the QLIE-31 and HUDS scales within 3 months from the start of therapy. The highest quality of life ratings were most often observed in the groups receiving levetiracetam and oxcarbazepine (83.3 and 72%, respectively), the highest frequency of low ratings among those taking carbamazepine and valproates (16.5 and 17%). Clinically significant psychoemotional disorders were more often observed with the use of topiramate (21.8%), valproates (21.4%) and carbamazepine (16.6%), much less frequently with oxcarbazepine (8.3%), and were absent during treatment with levetiracetam. There is a strong correlation between the quality of life and the effectiveness and side effects of therapy, psychoemotional disorders. The best indicators of quality of life were observed with the use of new generation antiepileptic drugs.
Keywords: epilepsy, antiepileptic drugs, quality of life.